Multimodal chiropractic care for migraine: A pilot randomized controlled trial. (March 2021) - Rist, Pamela M; Bernstein, Carolyn; Kowalski, Matthew; Osypiuk, Kamila; Connor, Julie P; Vining, Robert; Long, Cynthia R; Macklin, Eric A; Wayne, Peter M
Background: Spinal manipulation may reduce migraine frequency, but effects of multimodal chiropractic care on migraine frequency have not been evaluated. Methods: We conducted a pilot randomized controlled trial comparing multimodal chiropractic care + enhanced usual care (MCC+) versus enhanced usual care alone (EUC) among adult women with episodic migraine. EUC was comprised of usual medical care and migraine education literature. MCC+ participants received 10 sessions of chiropractic care over 14 weeks. Primary aims evaluated feasibility of recruitment, retention, protocol adherence, and safety. Change in migraine days was a secondary aim. Results: Of 422 patients screened, 61 were randomized over 20 months. Fifty-seven (93%) completed daily migraine logs during the intervention, 51 (84%) completed final follow-up, and 45 (74%) completed all assessments. Twenty-four of 29 MCC+ participants (83%) attended > 75% of the chiropractic sessions. Ninety-eight non-serious adverse events were reported by 26 participants (43%) with 39 events among 11 EUC participants and 59 events among 15 MCC+ participants. MCC+ participants experienced greater reductions in migraine days (−2.9 days for MCC+ vs. −1.0 days for EUC, difference = −1.9; 95% confidence interval: −3.5, −0.4). Conclusions: Pre-specified feasibility criteria were not met, but deficits were remediable. Preliminary data support a definitive trial of MCC+ for migraine. Trial Registration: This study is registered at Clinicaltrials.gov (NCT03177616).